Trimester-specific reference intervals of thyroid hormones for normal pregnant women at a tertiary care hospital in Mumbai, Maharashtra - Shahid A. Mujawar; Vinayak W. Patil; Rekha G. Daver (Al Ameen Medical College, 2019)
Background: Maternal thyroid dysfunction has been associated with ad¬verse pregnancy outcomes. Objectives: The present study was conducted to determine trimester-specific reference intervals (TRIs) for serum thyroid stimulating hormone (TSH), total circulating thyroxine (TT4), total circulating triiodothyronine (TT3), free triiodothyronine (FT3) and free thyroxine (FT4) on healthy pregnant women in Mumbai region. Materials and Methods: A case-control study designed with 50 normal pregnant women that randomly selected from the first (20 samples), the second (13 samples), and the third (17 samples) trimesters and 50 randomly selected non-pregnant healthy controls. Thyroid function tests were estimated by chemiluminescent immunoassay method. Results: TRIs of TSH, TT3, TT4, FT3 and FT4 for first trimester pregnancies were 0.45-3.11µIU/mL, 139-222 ng/dL, 9.24-19.2µg/dL, 1.87-5.40 pg/mL, and 1.06-1.66 ng/dL respectively. TRIs for second trimester pregnancies were 0.63-3.88 µIU/mL, 150-231 ng/dL, 8.75-18.0 µg/dL, 2.40-3.58 pg/mL, and 0.79-1.41 ng/dL. TRIs for third trimester pregnancies were 0.75-3.92 µIU/mL, 162-252 ng/dL, 7.91-14.3 µg/dL, 2.10-2.98 pg/mL, and 0.72-1.34 ng/dL. TRIs for TSH, TT3, TT4, FT4 and FT3 were different from non-pregnant normal reference intervals. Conclusions: The reference intervals of thyroid function tests in pregnant women differ among trimesters.